2021
DOI: 10.1371/journal.pone.0252763
|View full text |Cite
|
Sign up to set email alerts
|

Post-infectious and post-acute sequelae of critically ill adults with COVID-19

Abstract: Background Data on the post-acute and post-infectious complications of patients who have recovered from severe coronavirus disease 2019 (COVID-19) are limited. While studies report that approximately 5–15% of COVID-19 hospitalized patients require intensive care and mechanical ventilation, a substantially higher number need non-invasive ventilation and are subject to prolonged hospitalizations, with long periods of immobility and isolation. The purpose of this study is to describe the post-infectious sequelae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
(33 reference statements)
1
9
0
Order By: Relevance
“…Recently, in patients with COVID-19, astrocytic and neural injury markers have been correlated to COVID-19 severity but failed to predict subsequent long-term neurological outcomes (Kanberg et al, 2021). However, that study did not show a correlation of neurological outcome symptoms with disease severity which has been shown in several trials (Hopkins and Brett, 2005;Hopkins and Jackson, 2006;Herridge et al, 2016;Ibrahim et al, 2021). While it is clear that ICU level care and disease severity (likely associated with higher levels of peripheral inflammation and hypoxemia) in both patients with COVID-19 and pre-COVID historical patients is associated with both neurological sequelae and elevated brain injury, infection with SARS-CoV2 infection itself appears to markedly increase the likelihood of developing subsequent neurological symptoms.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, in patients with COVID-19, astrocytic and neural injury markers have been correlated to COVID-19 severity but failed to predict subsequent long-term neurological outcomes (Kanberg et al, 2021). However, that study did not show a correlation of neurological outcome symptoms with disease severity which has been shown in several trials (Hopkins and Brett, 2005;Hopkins and Jackson, 2006;Herridge et al, 2016;Ibrahim et al, 2021). While it is clear that ICU level care and disease severity (likely associated with higher levels of peripheral inflammation and hypoxemia) in both patients with COVID-19 and pre-COVID historical patients is associated with both neurological sequelae and elevated brain injury, infection with SARS-CoV2 infection itself appears to markedly increase the likelihood of developing subsequent neurological symptoms.…”
Section: Discussionmentioning
confidence: 89%
“…Other cohort studies reporting outcomes at 4 to 6 months found inconclusive results related to the impact of the type of ward patients were admitted to [8,11]. It is well known that a stay in ICU is related to a higher prevalence of muscle weakness and exercise limitation at hospital discharge [6,36,37]. However, the patients admitted to ICU in our sample were younger and had a lower level of frailty at baseline, suggesting that the poor outcomes observed at discharge were reversible, in contrast with what observed for patients with previous frailty.…”
Section: Discussionmentioning
confidence: 99%
“…HRQOL was assessed using the French version of the SF-36 survey, which is composed of one item related to changes in health during the previous year and 35 items within 8 categories: (1) physical functioning, (2) role limitations due to physical health, (3) pain, (4) general health, (5) emotional well-being, (6) role limitations due to emotional problems, (7) vitality, and (8) social functioning. The total score ranges from 0 to 100, with a higher score indicating a better health status [21,22].…”
Section: Measurements and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Long-COVID syndrome, coughing and dyspnea are prominent, lasting for several months, with coughing been present in 15% to 42% of patients [7,[11][12][13]. The supplemental oxygen requirement for post-acute COVID-19 infection ranges from no requirements to up to 50% of patients being discharged on oxygen, and this wide variation is likely due to the time-frame of the study, as most patients will not require oxygen after 4 to 6 months post-infection [14,15]. Factors reported to be predictive of post-COVID syndrome are female sex, severity of acute infection, and the presence of respiratory comorbid conditions [12,13,16].…”
Section: Discussionmentioning
confidence: 99%